The Role of Artificial Intelligence in Promoting Employee Workplace Green Behaviors: A Systematic Analysis - Danzen Olazo; Joy Anne Evaristo (SEISENSE Business Review)
This systematic literature review explores the intersection of artificial intelligence (AI) and employee workplace green behaviors, examining how AI interventions can enhance sustainable practices in organizations. The paper addresses three primary research questions: (1) What role does AI play in promoting employee workplace green behaviors? (2) How is AI currently applied to enhance green behaviors within organizational settings? and (3) What are the barriers or enablers for AI-driven interventions in fostering green behaviors? A comprehensive search strategy was employed, identifying key studies on AI applications in sustainability and employee behaviors. The findings suggest that AI can drive green behaviors through smart resource management, behavior tracking, and decision-making support, while highlighting barriers such as technological limitations and organizational resistance. The paper concludes with recommendations for organizations seeking to leverage AI for sustainability and discusses the theoretical and practical implications of AI in fostering environmentally responsible workplace practices.